2016
DOI: 10.1097/iae.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Multimodal Imaging After Idiopathic Epiretinal Membrane Surgery

Abstract: Adaptive optics imaging gives new insight into the changes of vitreomacular interface after iERM surgery. Enhanced multimodal imaging of the vitreomacular interface and retinal structures can be valuable to monitor treatment outcome of iERM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Adaptive optics scanning laser ophthalmoscopy has been used by researchers to examine the retina in patients with ERM. Macrofolds, microfolds (5‐10 μm) and hyper‐reflective microstructures of the vitreomacular interface have been seen to resolve or redistribute after surgical ERM peeling 124 . These hyper‐reflective microstructures have been observed in other retinal and even neurological conditions, raising the possibility that they represent reactive gliosis in the inner retinal layers 125‐129 …”
Section: Investigationsmentioning
confidence: 99%
“…Adaptive optics scanning laser ophthalmoscopy has been used by researchers to examine the retina in patients with ERM. Macrofolds, microfolds (5‐10 μm) and hyper‐reflective microstructures of the vitreomacular interface have been seen to resolve or redistribute after surgical ERM peeling 124 . These hyper‐reflective microstructures have been observed in other retinal and even neurological conditions, raising the possibility that they represent reactive gliosis in the inner retinal layers 125‐129 …”
Section: Investigationsmentioning
confidence: 99%
“… 8 Other studies have reported the persistence of subfoveal tractional abnormalities despite surgical removal of tractional membranes. 11 The purpose of the current study is to report the clinical and anatomic outcomes of eyes with tractional abnormalities of the central foveal bouquet (CB) due to idiopathic epiretinal membranes (iERMs).…”
Section: Introductionmentioning
confidence: 99%